Carbapenemase-producing Enterobacteriaceae in transplant patients. (27th January 2021) - Giannella, Maddalena; Bartoletti, Michele; Conti, Michela; Righi, Elda
Abstract: Carbapenemase-producing Enterobacteriaceae (CPE) are a serious public health concern and represent a major threat to immunocompromised hosts, including solid organ (SOT) and stem cell transplant (HSCT) recipients. Transplant patients are at particular risk of developing CPE colonization and/or infection due to their frequent exposure to prolonged courses of broad-spectrum antibiotics, altered immunocompetence and exposure to invasive procedures and immunosuppressive drugs. Gut colonization with CPE, in particular carbapenem-resistant Klebsiella pneumoniae, may occur before or after SOT in 2%–27% of patients and among 2%–9% of HSCT and has been associated with increased risk of developing CPE infections. In endemic areas, CPE infections occur in up to 18% of SOT, and HSCT patients can account for 5%–18% of all patients with CPE bacteraemia. Mortality rates up to 70% have been associated with CPE infections in both patient populations. The rapid initiation of an active therapy against CPE is advocated in these infections. Therapeutic options, however, are limited by the paucity of novel compounds that are currently available and by potential antibiotic-associated toxicities. Therefore, a multidisciplinary approach involving infection control and antimicrobial stewardship programmes still represents the mainstay for the management of CPE infections among transplant patients. The evidence for the use of prevention strategies such as CPE-targeted perioperative prophylaxis or gut decolonization is still scarce. Large, multicentre trials are required to better define prevention strategies and to guide the management of CPE infections in the transplant setting.